Activation of somatostatin 2 receptors in the brain and the periphery induces opposite changes in circulating ghrelin levels: functional implications - Stengel, Andreas; Taché, Yvette F. (Frontiers in Endocrinology, 2013)
Somatostatin is an important modulator of neurotransmission in the central nervous system and acts as a potent inhibitor of hormone and exocrine secretion and regulator of cell proliferation in the periphery. These pleiotropic actions occur through interaction with five G-protein coupled somatostatin receptor subtypes (sst1-5) that are widely expressed in the brain and peripheral organs. The characterization of somatostatin’s effects can be investigated by pharmacological or genetic approaches using newly developed selective sst agonists and antagonists and mice lacking specific sst subtypes. Recent evidence points towards a divergent action of somatostatin in the brain and in the periphery to regulate circulating levels of ghrelin, an orexigenic hormone produced by the endocrine X/A-like cells in the gastric mucosa. Somatostatin interacts with the sst2 in the brain to induce an increase in basal ghrelin plasma levels and counteracts the visceral stress-related decrease in circulating ghrelin in rats. By contrast, stimulation of peripheral somatostatin-sst2 signaling results in the inhibition of basal ghrelin release and mediates the postoperative decrease in circulating ghrelin in rats. The peripheral sst2-mediated reduction of plasma ghrelin is likely to involve a paracrine action of D-cell derived somatostatin acting on sst2 bearing X/A-like ghrelin cells in the gastric mucosa. The other member of the somatostatin family, named cortistatin, in addition to binding to sst1-5 also directly interacts with the ghrelin receptor and therefore may simultaneously modulate ghrelin release and actions at target sites bearing ghrelin receptors representing a link between the ghrelin and somatostatin systems.